2005
DOI: 10.2135/cropsci2005.0155
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Mobilization of Sulfur during Soybean Reproduction

Abstract: This manuscript has been reproduced from the microfilm master. UMI films the text directly from the original or copy submitted. Thus, some thesis and dissertation copies are in typewriter face, while others may be from any type of computer printer.The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely aflFect reproduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 126 publications
0
19
0
Order By: Relevance
“…The abundant RuBisCO enzyme is enriched in cysteine + methionine and threonine that increased under shade conditions here; however, not all amino acids that were found to increase in relative abundance under shade are enriched in RuBisCO (Schmitz-Linneweber et al, 2001). Naeve and Shibles (2005) demonstrated the dependence of seed protein on mobilized S from vegetative tissues. Together, this supports a possible role for vegetative reserves to support protein quality through enhancing the relative amounts of the limiting amino acids, which may be less C-dependent.…”
Section: Relationship Between Protein Concentration and Amino Acid Bamentioning
confidence: 56%
See 1 more Smart Citation
“…The abundant RuBisCO enzyme is enriched in cysteine + methionine and threonine that increased under shade conditions here; however, not all amino acids that were found to increase in relative abundance under shade are enriched in RuBisCO (Schmitz-Linneweber et al, 2001). Naeve and Shibles (2005) demonstrated the dependence of seed protein on mobilized S from vegetative tissues. Together, this supports a possible role for vegetative reserves to support protein quality through enhancing the relative amounts of the limiting amino acids, which may be less C-dependent.…”
Section: Relationship Between Protein Concentration and Amino Acid Bamentioning
confidence: 56%
“…Shade, however, tended to increase the relative abundance of lysine, methionine, cysteine, threonine, and histidine to a greater extent than expected based on these regressions. Naeve and Shibles (2005) demonstrated the dependence of seed protein on mobilized S from vegetative tissues. This lack of supplied C separates whole-plant source-sink conditions imposed by the shade treatment from the other treatments that resulted in higher protein concentration, open environment, and pod removal.…”
Section: Relationship Between Protein Concentration and Amino Acid Bamentioning
confidence: 99%
“…Sunarpi and Anderson (1998) described S redistribution in S-deficient vegetative soybean (with an 35 S pulse–chase labelling method) and reported that ∼25% of the mobilized S was recycled as 34 SO 4 2− via the root and the largest newly expanded leaf, which acts as an intermediary in the transport of S from the root to the youngest expanding leaves. S mobilization in suboptimal conditions of S fertilization was also examined in reproductive soybean (Sunarpi and Anderson, 1997; Naeve and Shibles, 2005). These authors reported that soybean leaves did not act as large reservoirs for S in conditions of suboptimal S fertilization.…”
Section: Introductionmentioning
confidence: 99%
“…These authors reported that soybean leaves did not act as large reservoirs for S in conditions of suboptimal S fertilization. Nevertheless, under SO 4 2− -sufficient conditions, it was shown that leaves of soybean supplied the seed with 20% of its total S requirement (Naeve and Shibles, 2005). Therefore, in soybean, the amount of S mobilized from leaves at the reproductive stage appears to be reliant on the amount previously stored in roots and leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Assimilation of transported S -methyl-Met requires homocysteine as an acceptor of the S -methyl group. Under sulphur-sufficient conditions, soybean seeds do accumulate detectable levels of sulphate throughout development (Naeve and Shibles, 2005). Recent functional genomic studies have highlighted the occurrence of complete pathways of sulphate assimilation and de novo Cys and Met biosynthesis in developing seed, both in soybean and common bean (Yi et al ., 2010; Yin et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%